2014
DOI: 10.7860/jcdr/2014/7389.4030
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Absence of Flexor Digitorum Superficialis Tendon of the Little Finger: Clinical Significance

Abstract: The flexor digitorum superficialis (FDS/sublimis) is a flexor of the digits of the hand and has been reported to have varying degrees of agenesis. During routine cadaveric dissection for undergraduates at SRMS-IMS Bareilly, India, we observed bilateral absence of the FDS tendon to little finger in the upper limbs of a 45-year-old male cadaver. The muscle was normally supplied by a branch of median nerve in the forearm. Variants of the FDS muscle of the little finger have been reported in the literature. Proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 10 publications
(5 reference statements)
0
15
0
3
Order By: Relevance
“…There are many described variations of the FDS [1,3,5,[7][8][9][10], and suspicion of these variations preoperatively and identification intraoperatively is important for accurate diagnosis and tendon repair. The FDS independent variation, where the small finger FDS tendon inserts on to the middle phalanx of the small finger independently without direct connections to the ring finger tendon, is the most common variant of the FDS [2,5,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are many described variations of the FDS [1,3,5,[7][8][9][10], and suspicion of these variations preoperatively and identification intraoperatively is important for accurate diagnosis and tendon repair. The FDS independent variation, where the small finger FDS tendon inserts on to the middle phalanx of the small finger independently without direct connections to the ring finger tendon, is the most common variant of the FDS [2,5,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The primary action of FDS is to flex the middle phalanx at the proximal interphalangeal (PIP) joints and can also flex the metacarpal phalangeal (MCP) joints and wrist joint with sustained action [1,3]. This allows the human hand to make skilled, grasping movements necessary for fine motor skills [3][4]. For instance, Gupta and Kumar found that the independent function of the FDS tendons was essential for high caliber, professional musicians [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations